To simplify the expression \((z+4)(z−4)\), we can use the difference of squares formula, which states that \((a + b)(a - b) = a^2 - b^2\).
Here, \(a = z\) and \(b = 4\).
So we have:
\[ (z + 4)(z - 4) = z^2 - 4^2 = z^2 - 16 \]
Now, let's evaluate the choices provided:
- z² - 8z - 16: This is incorrect.
- z(z) + 4z(z) - 4(4): This simplifies to \(z^2 + 4z^2 - 16\), which is also incorrect.
- 2z² - z² - 8: This simplifies to \(z² - 8\), which is incorrect.
- z² + 4z - 4z - 16: This simplifies to \(z² + 0 - 16 = z² - 16\), which is correct.
Thus, the equivalent expression to \((z+4)(z−4)\) is:
z² - 16.
The closest option is z² + 4z - 4z - 16, which simplifies to z² - 16.